(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the scientific and pedagogical foundations and effective ways of forming ecological culture and education in students at the primary education stage. Ecological education is considered as a continuous process aimed at developing a person’s conscious attitude to nature, a careful approach to the environment, and skills for the rational use of natural resources. Taking into account the psychological characteristics of younger schoolchildren (curiosity, tendency to emotional perception), the mechanisms of using integrated, interactive methods in the educational process: excursions, game exercises, project work, and ecological fairy tales are highlighted. The article provides practical recommendations for increasing the effectiveness of ecological education.